Adsorptive removal of antibiotics from water using peanut shells from agricultural waste. Issue 24 (11th April 2018) - Li, Rui; Zhang, Yuling; Chu, Wenlei; Chen, Zaixing; Wang, Jiali
Abstract : The porous structure of the materials was determined using the surface area and pore size analyzer (JW-BK132F) by N2 adsorption–desorption isotherms at 77 K. Abstract : The residues of sulfonamides in the environment have received widespread attention because of their potential hazards. In this study, the potential of peanut shells for antibiotic removal from aqueous solutions was investigated for four antibiotics (sulfamerazine, sulfamethazine, sulfathiazole, and sulfamethoxazole). The properties of the peanut shells were characterized using Brunauer–Emmett–Teller method, X-ray photoelectron spectroscopy, scanning electron microscopy and Fourier-transform infrared spectroscopy analyses, and the results of the analyses showed that the significant properties of peanut shells were mainly attributed to the antibiotics' adsorption process. A batch adsorption experiment was conducted to study the effect of dosage, concentration, and water factors (Fe 3+, Mn 2+, and Ca 2+ ) on antibiotic adsorption. Adsorption kinetics and isotherms were also studied. The kinetic data showed that a pseudo-second order kinetic model fitted the experimental data, the adsorption isotherm experimental data fitted the Henry linear adsorption model well, and methanol was found to be an effective eluent for desorption of the antibiotics. The results indicate that peanut shells are a promising material for the removal of antibiotics from contaminated water, when present at low initial concentrations.